2018
DOI: 10.1080/23802359.2018.1501311
|View full text |Cite
|
Sign up to set email alerts
|

Complete plastome sequence of Paeonia lactiflora Pall. (Paeoniaceae: Saxifragales)

Abstract: Paeonia lactiflora has been listed as an Endangered species in Russian Federation. The complete plastome was assembled from Next-Generation Sequencing data. It is 152,747 bp in length. It consists of a pair of Inverted Repeat regions (25,651 bp), separated by a small single copy region of 17,033 bp and a large single copy region of 84,412 bp. The plastome encoded 128 genes, including 83 protein coding genes, 37 tRNA, eight rRNA genes, four pseudogenes, and is characterized by loss of the rpl32 and infA genes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…In this study, comparative analysis showed that these two gene loss events occurred in all eleven plastomes of Paeoniaceae. A possible explanation is that the two functional genes have been transferred to the nucleus [8,47,54,55,56,57,58,59,60]. Furthermore, Dong et al [8] observed that the intron of rpl2 was completely lost in Saxifraga stolonifera .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, comparative analysis showed that these two gene loss events occurred in all eleven plastomes of Paeoniaceae. A possible explanation is that the two functional genes have been transferred to the nucleus [8,47,54,55,56,57,58,59,60]. Furthermore, Dong et al [8] observed that the intron of rpl2 was completely lost in Saxifraga stolonifera .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, all published five P. lactiflora and three P. veitchii complete chloroplast genomes in GenBank database were simultaneously taken into consideration for comparative analyses ( Zhang et al, 2016 ; Samigullin et al, 2018 ; Lee et al, 2019 ; Gao et al, 2020 ; Tables 2 , 3 ). The result showed that the two Chishao chloroplast genomes exhibited high similarity with previously published data in genome size and structure, gene number, as well as GC content.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we (1) sequenced, assembled, and annotated the complete chloroplast genome sequence of P. lactiflora and P. veitchii from our herbal materials, and compared them with those reported previously in terms of genome size, gene structure and guanine-cytosine (GC) content ( Zhang et al, 2016 ; Samigullin et al, 2018 ; Lee et al, 2019 ; Gao et al, 2020 ), and then search for hypervariable regions in protein-coding sequences to design mini-barcodes; (2) to combine the mini-barcode with DNA metabarcoding method to examine whether the former could be used for the qualitative and quantitative analysis of P. lactiflora and P. veitchii ; (3) take “cerebral thrombosis tablets” as an example to confirm the applicability of designed mini-barcode in proprietary Chinese medicines.…”
Section: Introductionmentioning
confidence: 99%
“… 2023 ), P. lactiflora MZ636553 (unpublished), P. mairei MZ617462 (unpublished), P. veitchii NC_032401 (Samigullin et al. 2018 ), P. intermedia MT210547 (Chen et al. 2023 ), P. ovovata NC_026076 (Samigullin et al.…”
Section: Resultsmentioning
confidence: 99%